Computational study of how inert additives affect the flammability of a polymer. (June 2019) - Roenner, Nils; Yuan, Han; Krämer, Roland H.; Rein, Guillermo
Abstract: All polymers are flammable to some degree. For safety, polymer flammability is most commonly reduced through flame retardants that are designed to primarily act chemically as opposed to physically. Here, we investigate computationally using the code Gpyro how inert additives such as hollow glass spheres (HGS) and boron nitride platelets (BNP) alter the flammability properties of glass fibre reinforced polybutylene terephthalate (PBT-GF), in a cone heater and UL94 setup. The Gpyro model is first validated against experiments and another code, both from the literature, for pure PBT-GF. According to the predictions, HGS leads to higher surface temperatures but lower temperatures in-depth, whereas adding BNP yields the opposite effect. Modelling numerically the cone heater setup shows that at 50% HGS loading, the time to ignition is reduced to a quarter while the semi-steady state mass loss rate is reduced to a third; at 50% BNP loading, the time to ignition is doubled while the peak mass loss rate is approximately doubled. In the UL94 setup, where the sample is smaller than cone heater, the effects are similar although less pronounced. A sensitivity study of the thermophysical properties shows that time to ignition is primarily controlled by emissivity, density and specific heat capacity, while peak mass loss rate is controlled by thermal conductivity and specific heat capacity. This work shows how heat transfer within a thermoplastic polymer can be utilised to improve its flammability characteristics through inert additives as well as the limitations of this retardancy approach. Highlights: Inert additives can modify the flammability of polymers by means of heat transfer. Adding 50% glass spheres reduces time to ignition by 75% but decreases mass loss rate. Adding 50% boron nitride platelets doubles time to ignition but increases mass loss rate. Additives targeting only the specific heat capacity can decrease the overall flammability of polymers. Synergies of chemically and heat transfer active flame retardants should be explored.